A cache-aware social-based QoS routing scheme in Information Centric Networks. (1st November 2018) - Qu, Dapeng; Wang, Xingwei; Huang, Min; Li, Keqin; Das, Sajal K.; Wu, Sijin
Abstract: Due to the rapid expansion of Internet and the huge proliferation of users, Internet has evolved from a host-centric model to a content-oriented model. This implies the in-adaptation of current TCP/IP architecture providing the best performance to end-users and the urgency of researching future Internet architecture. In future Internet, the named data rather than traditional IP address may become the thin waist of the hourglass model of networking. Therefore, in this paper, we propose a cache-aware social-based Quality of Service (QoS) routing scheme for Named Data Networking (NDN) in Information Centric Network (ICN). Three kinds of social relationships, namely neighbors ( NB ), interest friends ( IF ) and response friends ( RF ) are devised to describe the relationships among nodes. Thus, when there is a failure in doing Pending Interest Table (PIT) scheme, a forwarding scheme based on social relationships is done before doing Forwarding Information Base (FIB) scheme. Moreover, a caching policy and its corresponding replacement policy based on content popularity, cache space and neighbor caching information are proposed. Results from simulation experiments demonstrate that our proposed scheme has better performance, including a higher routing success ratio, than NDN routing mechanism.